CONSIDERATIONS FOR SURGICAL PLANNING OF HUMERAL OSTEOTOMY IN BRACHIAL PLEXUS BIRTH PALSY BASED ON THE ELBOW CREASE AND HUMERAL RETROVERSION MEASUREMENT - Ivalde, Flavio Cesar; Marazita-Valverde, Jose; Bataglia, Danilo (Journal of Ayub Medical College Abbottabad, 2019)
In obstetric brachial plexus, injuries are characterized by contractures, weakness and an association with different bone deformities, such as elongation of the coracoid process and/or acromion, retroversion of the glenoid cavity, flattening of the humeral head and Scapular Hypoplasia with Elevation and Rotation (SHEAR). Another humeral deformity is the retroversion of the humeral head, cases of which are increased in the presence of plexus lesions. The purpose of the current manuscript is to highlight two aspects of this latter deformity. First, the importance of taking into consideration the reduction of a humeral retroversion as a quantifiable bone deformity (by medical imaging technique) along with the other bone deformities previously mentioned. Finally, the complementation of these measurements by the clinical measures of the anterior crease of the elbow to rebuild the plane of motion to a level comparable to that of the healthy side, thereby avoiding excessive exorotation, would facilitate and improve the planning of surgical strategies for each patient.